IMPACT OF THE NEW LAW ON PUBLIC BIDDING AND PURCHASES IN MUNICIPALITIES IN THE STATE OF TOCANTINS - de Paiva Ferreira, Gilson (Revista Gênero e Interdisciplinaridade, 2024)
This article aims to present a field research with the theme: “Impact of the new law on public bidding and procurement in municipalities in the state of Tocantins. This article explores the impacts of Law No. 14,133/2021, the new Bidding Law, in the context of public procurement in the State of Tocantins, through qualitative and field research. The legislation introduces significant changes aimed at improving efficiency and transparency in bidding processes, directly impacting the government and companies. At the government level, the highlights are reducing bureaucracy, encouraging innovation, and introducing modalities such as competitive dialogue. For companies, the law provides greater legal certainty, predictability in procurement, and facilitates the participation of foreign companies, promoting sustainable practices. The research in Tocantins, based on interviews with 21 professionals and public managers, reveals perceptions about adaptation to the new legislation and the challenges faced. The authors cited contribute with theoretical and practical analyses that enrich the understanding of the effects of the law on public administration and the private sector: Matos, M.C. (2021) org, Abrucio, F. L (2021) Fernandes, R. (2022), Dias, M. A.(2022). Despite the limitations of the study, the new bidding legislation in Tocantins, although challenging, opens doors for administrative modernization, and despite limited resources, it is positively impacting local development, but still needs investment in training and readjustment in planning. Finally, the conclusions also point to the need for future research that explores the adaptability of these interventions in different institutions.